The Impact of The "Dual Carbon" Target on China’s Coal Industry Stock Prices–Analysis Based on The Double Difference Method - Yi, Ran; Zhang, Kaili; Feng, Xinru (Transactions on Economics, Business and Management Research, 2024)
The proposal of "dual-carbon" target has far-reaching impacts on the coal industry and its stock market. This paper takes the data of China’s A-share coal listed companies in Shanghai and Shenzhen from 2018 to 2023 as samples, takes the proposal of "dual-carbon" target as an exogenous event, and uses double-difference model to conduct regression analysis to study the impact of "dual-carbon" target on the stock price of China’s coal industry. The results show that the introduction of the "dual carbon" target has a significant negative impact on the stock price of China’s coal industry, and the results are still significant after the parallel trend test, the placebo test, and the test of excluding the year of policy promulgation. Based on this, recommendations are made for the government, regulators, coal industry enterprises and investors to jointly promote the development of the "dual-carbon" policy and the transformation and upgrading of the coal industry.